2012
DOI: 10.1021/ja3013177
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Synthesis of Intentionally Misfolded Homogeneous Glycoprotein: A Unique Approach for the Study of Glycoprotein Quality Control

Abstract: Biosynthesis of glycoproteins in the endoplasmic reticulum employs a quality control system, which discriminates and excludes misfolded malfunctional glycoproteins from a correctly folded one. As chemical tools to study the glycoprotein quality control system, we systematically synthesized misfolded homogeneous glycoproteins bearing a high-mannose type oligosaccharide via oxidative misfolding of a chemically synthesized homogeneous glycopeptide. The endoplasmic reticulum folding sensor enzyme, UDP-glucose:glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
51
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 32 publications
1
51
0
Order By: Relevance
“…Therefore, our research group concluded that UGGT recognizes these hydrophobic surfaces formed on the misfolded glycoprotein surface. 38 Our chemical approach confirmed that UGGT indeed recognizes the characteristic nature of misfolded glycoproteins, and this finding enabled us to consider how UGGT recognizes the glycoprotein folding intermediates in which hydrophobic amino acids may be exposed on the glycoprotein. There are many folding intermediates, such as the random coil structure 46, native form folded 48, misfolded form 50, and heavily aggregated 51 in the course of the folding process ( Figure 9A), and some of these folding intermediates are in equilibrium with each other.…”
supporting
confidence: 59%
See 2 more Smart Citations
“…Therefore, our research group concluded that UGGT recognizes these hydrophobic surfaces formed on the misfolded glycoprotein surface. 38 Our chemical approach confirmed that UGGT indeed recognizes the characteristic nature of misfolded glycoproteins, and this finding enabled us to consider how UGGT recognizes the glycoprotein folding intermediates in which hydrophobic amino acids may be exposed on the glycoprotein. There are many folding intermediates, such as the random coil structure 46, native form folded 48, misfolded form 50, and heavily aggregated 51 in the course of the folding process ( Figure 9A), and some of these folding intermediates are in equilibrium with each other.…”
supporting
confidence: 59%
“…Segment 1 (1 33 position), the peptide-α-thioester, and segment 2 (3472 position), a glycopeptide bearing a high-mannose-type oligosaccharide at the 36 position, were successfully synthesized by Boc-SPPS and Fmoc-SPPS, respectively, and subsequent NCL yielded the target glycosylpolypeptide 42 ( Figure 8A). 38 All of the synthetic intermediate and the target glycosylpolypeptide 42 were analyzed by ESI-mass spectrometry.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…13) Recently, Kajihara's group reported the synthesis of interleukin-8 and crambin carrying M9 glycan (M9-IL8 14) and M9-crambin 15) ) by the NCL method. The ability of UGGT to discriminate glycoprotein's folding status was confirmed by using conformers of M9-IL8 that were prepared by swapping of the disulfide linkage.…”
Section: Synthetic Glycoproteinsmentioning
confidence: 99%
“…More recently, Kajihara's group achieved the synthesis of an intentionally misfolded glycoprotein as a structurally defined, homogeneous substrate of UGGT. 51) They selected IL-8 as a model, modified by M9 at Asn36 (M9-IL-8). Synthesis was achieved by native chemical ligation of two segments, a 1-33 thioester and a 34-72 glycopeptide.…”
Section: Analysis Of Uggt a Folding Sensor In The Ermentioning
confidence: 99%